2015
DOI: 10.1016/j.tvjl.2015.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Gene network and canonical pathway analysis in canine myxomatous mitral valve disease: A microarray study

Abstract: Myxomatous mitral valve disease (MMVD) is the single most common acquired heart disease of the dog and is particularly common in small pedigree breed dogs such as the Cavalier King Charles spaniel (CKCS). There are limited data on the mitral valve transcriptome and the aim of this study was to use the microarray technology in conjunction with bioinformatics platforms to analyse transcript changes in MMVD in CKCS compared to normal dogs (non-CKCS). Differentially expressed genes (n = 5397) were identified using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
112
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(117 citation statements)
references
References 54 publications
5
112
0
Order By: Relevance
“…There are limited tissue gene expression data for canine MMVD, but one study reported the transcriptomic pro le of aged CKCS with advanced disease [18]. The analysis found that the most affected biologically relevant functions were in ammatory/immune response, cellular movement, cardiovascular development, extracellular matrix organization and epithelial-to-mesenchymal transition (EMT), not dissimilar to the one other canine report not involving CKCSs [18,19].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…There are limited tissue gene expression data for canine MMVD, but one study reported the transcriptomic pro le of aged CKCS with advanced disease [18]. The analysis found that the most affected biologically relevant functions were in ammatory/immune response, cellular movement, cardiovascular development, extracellular matrix organization and epithelial-to-mesenchymal transition (EMT), not dissimilar to the one other canine report not involving CKCSs [18,19].…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, there is evidence of enhanced 5HT signalling in both human and canine MMVD valve tissue and valve interstitial cells (VIC) exposed to tensile strain, and genetic variation in the exons of the 5HT transporter gene (SLC6A4, also known as SERT) may be associated with MMVD development in the Maltese terrier [16,17]. Changes in expression of the 5HT receptor gene are reported for the canine mitral valve transcriptome, and in the dog HTR2B expression is associated with disease progression [18][19][20][21]. However, 5HT does not induce disease phenotype in cultured VICs and expression of 5HT receptor genes is controlled by TGFβ1 [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of 5-HT 2B receptors in human VICs is mitogenic, resulting in ERK1/2 phosphorylation and incorporation of [ 3 H]deoxythymidine (Setola et al, 2003) and has also been implicated in 5-HT-induced valvulopathy in experimental animals (Elangbam et al, 2008). The 5-HT 2B receptor appears enriched in heart valves from various species including dog (Oyama and Chittur, 2006;Lu et al, 2015;Cremer et al, 2015a), rat (Elangbam et al, 2005), pig (Fitzgerald et al, 2000;(Cremer et al, 2015b) and human (Fitzgerald et al, 2000), mainly in healthy tissues. Nevertheless, 5-HT receptors other than the 5-HT 2B subtype have been reported in valve tissue (Lu et al, 2015;Cremer et al, 2015b), and the involvement of the 5-HT transporter (SERT) in VHD has been suggested by the development of valvular fibrosis in SERT knockout (KO) mice (Mekontso-Dessap et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The 5-HT 2B receptor appears enriched in heart valves from various species including dog (Oyama and Chittur, 2006;Lu et al, 2015;Cremer et al, 2015a), rat (Elangbam et al, 2005), pig (Fitzgerald et al, 2000;(Cremer et al, 2015b) and human (Fitzgerald et al, 2000), mainly in healthy tissues. Nevertheless, 5-HT receptors other than the 5-HT 2B subtype have been reported in valve tissue (Lu et al, 2015;Cremer et al, 2015b), and the involvement of the 5-HT transporter (SERT) in VHD has been suggested by the development of valvular fibrosis in SERT knockout (KO) mice (Mekontso-Dessap et al, 2006). Moreover, the wellknown 'carcinoid heart', a valvulopathy associated with excess of plasma (free) 5-HT secreted by neuroendocrine tumours, highlights the important role of this biogenic amine in VHD (Lundin et al, 1988).…”
Section: Introductionmentioning
confidence: 99%